The Effect of Professional Ethics, Locus of Control, and Auditor Expertiseon Audit Judgement - Viona Cornelia; Amanda Aulia; Kayla Nurhaliza (Journal of Accounting and Auditing, 2025)
Purpose – This study aims to astudy, analyze and obtain empirical evidence regarding how professional ethics, locus of control, and auditor expertise influence audit judgement. Design/methodology/approach – This research uses quantitative research methods, using primary data collected from population of 38 Office of Public Accountant, including companies/agencies that work as internal auditors or external auditors. This data analysis was carried out using Partial Least Square (PLS) software with Moderated Regression Analysis. Findings – This study has the result that professional ethics significantly influences audit judgement and locus of control does not significantly influence audit judgement, then auditor expertise does not significantly influence audit judgement. Research limitations/implications – There are several limitations in this study that should be considered when explaining the results. First, the sample size is limited to 38 internal auditors and external auditors working at Office of Public Accountant, including agencies/companies which may not fully represent the general auditor population. This may limit the generalizability of the findings of this study. Second, this study uses a survey method with a questionnaire as a data collection tool, which may be prone to respondent bias, such as desirable social bias or inaccuracy in filling out the questionnaire. Third, this study only considered three main variables, namely professional ethics, locus of control, and auditor expertise, so other factors that might affect audit judgment, such as time pressure, work experience, or organizational culture, were not analyzed in depth.   Therefore, the implications for future research need to be interpreted with caution and serve as a basis for further research that includes a wider sample, additional variables, as well as more diverse methodological approaches.